Inflammatory cytokines in major depressive disorder: A case–control study. (January 2017) - Cassano, Paolo; Bui, Eric; Rogers, Andrew H; Walton, Zandra E; Ross, Rachel; Zeng, Mary; Nadal-Vicens, Mireya; Mischoulon, David; Baker, Amanda W; Keshaviah, Aparna; Worthington, John; Hoge, Elizabeth A; et al.
Introduction: There is mixed evidence in the literature on the role of inflammation in major depressive disorder. Contradictory findings are attributed to lack of rigorous characterization of study subjects, to the presence of concomitant medical illnesses, to the small sample sizes, and to the limited number of cytokines tested. Methods: Subjects aged 18–70 years, diagnosed with major depressive disorder and presenting with chronic course of illness, as well as matched controls ( n  = 236), were evaluated by trained raters and provided blood for cytokine measurements. Cytokine levels in EDTA plasma were measured with the MILLIPLEX Multi-Analyte Profiling Human Cytokine/Chemokine Assay employing Luminex technology. The Wilcoxon rank-sum test was used to compare cytokine levels between major depressive disorder subjects and healthy volunteers, before (interleukin [IL]-1β, IL-6, and tumor necrosis factor-α) and after Bonferroni correction for multiple comparisons (IL-1α, IL-2, IL-3, IL-4, IL-5, IL-7, IL-8, IL-10, IL-12(p40), IL-12(p70), IL-13, IL-15, IFN-γ-inducible protein 10, Eotaxin, interferon-γ, monotype chemoattractant protein-1, macrophage inflammatory protein-1α, granulocyte-macrophage colony-stimulating factor and vascular endothelial growth factor). Results: There were no significant differences in cytokine levels between major depressive disorder subjects and controls, both prior to and after correction for multiple analyses (significance set at p  ⩽ 0.05 and p  ⩽ 0.002, respectively). Conclusion: Our well-characterized examination of cytokine plasma levels did not support the association of major depressive disorder with systemic inflammation. The heterogeneity of major depressive disorder, as well as a potential sampling bias selecting for non-inflammatory depression, might have determined our findings discordant with the literature.